The Importance Of Extracurricular And External Activities In Students' Personal Development - Jurayeva Dilafruz Jamurodovna (Genius Publishing Group, 2024)
This article describes the theoretical foundations of correct and effective organization of extracurricular activities in the development of intellectual, spiritual, moral and creative thinking of students. Extracurricular activities complement the learning activities of students. This helps them to shape their world view and develop their morale. Theoretical knowledge is closely linked to practical production. The role of a facilitator in managing extracurricular activities is also multifaceted.
Keywords: Spirituality; Superiority; Educational Work; Thinking